A CASE OF ACUTE MESENTERIC ISCHEMIA: DIAGNOSTIC DILEMMA AND SURGICAL CHALLENGE - MITTAL, MOHIT; GAUR, NIMISH; GHODKE, SANDHYA; HIREMATH, RAVISHEKAR N; BASRA, SHARANJIT SINGH; VERMA, VISHAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Mesenteric ischemia is an uncommon condition, and we need to have a high index of suspicion to diagnose and manage this condition. Predisposing conditions such as myocardial infarction, portal hypertension, pancreatitis, inflammatory bowel disease, post-operative states, trauma, and hypercoagulable states such as DVT, pregnancy, and neoplasms should always be accounted for before diagnosing this condition. In emergency situations, surgical exploration is warranted. Here, we present a case of 57-year-old male, known case of DVT RT lower limb, on anticoagulants, presented with the complaints of epigastric pain, absolute constipation, and abdominal distention of 3 days duration. He was investigated and managed by exploratory laparotomy with peritoneal lavage and resection of gangrenous bowel with proximal jejunostomy and distal ileostomy.